A Multicenter Study Using the SWAG Scale to Compare Secondary Alveolar Bone Graft Outcomes for Patients with Cleft Lip and Palate. (March 2016) - Russell, Kathleen; Long, Ross E.; Daskalogiannakis, John; Mercado, Ana; Hathaway, Ronald; Semb, Gunvor; Shaw, William
Objective: To assess secondary alveolar bone graft (ABG) outcomes using the standardized way to assess grafts, or SWAG scale, for patients with cleft lip and palate (CLP). Design: Retrospective cohort study. Setting: Four cleft centers with different protocols. Methods: One hundred sixty maxillary occlusal radiographs taken 3 to 18 months after secondary ABG for sequentially treated patients with CLP were assessed using the SWAG scale. Radiographs were scanned, standardized, blinded, and rated by six orthodontists using the SWAG scale. Randomized radiographs were rated twice, 24 hours apart, by the same raters. Main Outcomes: Intrarater and interrater reliabilities were assessed. Means and SDs were calculated for ABG ratings using analysis of variance and Tukey tests (P < .05). Result: The mean ABG age was 9.1 years (range = 7 to 10.1 years) and the mean follow-up age was 12.4 years (range = 8.2 to 20.4 years). Intrarater and interrater reliabilities were good (intrarater = 0.788, interrater = 0.705), and higher than published methods. Mean ABG ratings for the cleft centers were 4.53, 2.9, 3.63, and 5.0 and differed significantly. The two centers with the highest ABG ratings showed higher ratings for all thirds decreasing from apical to coronal. The two centers with lower ABG ratings showed poorer ABG ratings for all thirds, and the middle third received the highest ratings. Conclusions: The SWAG scale overcomes the challenges of age and bone location. The SWAG method was validated for showing intercenter differences for overall bone fill as well as in vertical thirds. Surgical technique, timing, and expertise/volume were identified as possible factors related to outcome.